The Influence of Production Management and Production Costs on Increasing Business Revenue of MSMEs in the Creative Product Sector in Gowa Regency - Suriyanti, Suriyanti; Amri, Fatchul; Kamal, Ayu Lestari; Rusdin, Andhika Putra; Sari, Khafifa (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the local economy, particularly in the creative product sector. Gowa Regency, as one of the regions with numerous MSMEs in this sector, faces challenges in increasing business income. One of the factors that can influence MSME income is production management and production costs. This study aims to examine the influence of production management and production costs on improving the business income of MSMEs in the creative product sector in Gowa Regency. Research data were collected from creative product MSMEs in Gowa Regency, registered under the Department of Cooperatives and MSMEs of Gowa Regency, and willing to participate as respondents. The study used primary data obtained through a survey method by distributing questionnaires to 75 respondents. Data analysis was conducted using multiple linear regression with a quantitative approach. The research findings indicate that: Production management has a positive and significant effect on the increase in business income of MSMEs in the creative product sector in Gowa Regency. This indicates that effective production management can enhance efficiency and business income.Production costs also have a positive and significant effect on the increase in business income of MSMEs in the creative product sector in Gowa Regency, suggesting that proper cost management can improve business profitability.